2015
DOI: 10.1371/journal.ppat.1005030
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1 Regulates IFI16 Mediated Nuclear Innate Sensing of Herpes Viral DNA and Subsequent Induction of the Innate Inflammasome and Interferon-β Responses

Abstract: The innate immune system pattern recognition receptors (PRR) are the first line of host defenses recognizing the various pathogen- or danger-associated molecular patterns and eliciting defenses by regulating the production of pro-inflammatory cytokines such as IL-1β, IL-18 or interferon β (IFN-β). NOD-like receptors (NLRs) and AIM2-like receptors (ALRs) are cytoplasmic inflammasome sensors of foreign molecules, including DNA. IFI16, a sequence-independent nuclear innate sensor ALR, recognizes episomal dsDNA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
119
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 41 publications
(99 reference statements)
6
119
0
2
Order By: Relevance
“…Alternatively, the ability of ICP0 to target IFI16 for degradation may rely on a posttranslational modification that is absent in HeLa cells, IFI16 may be sequestered from ICP0 by another interaction, or another cellular protein may bridge ICP0 and IFI16 to promote degradation of the latter. Interestingly, it was recently observed that HSV-1 infection is able to promote the degradation of IFI16 in BRCA1-expressing (184B5) but not BRCA1-deficient (HCC1937) mammary epithelial cells (44). BRCA1 is best characterized as a tumor suppressor and is mutated or dysfunctional in a variety of tumor-derived cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the ability of ICP0 to target IFI16 for degradation may rely on a posttranslational modification that is absent in HeLa cells, IFI16 may be sequestered from ICP0 by another interaction, or another cellular protein may bridge ICP0 and IFI16 to promote degradation of the latter. Interestingly, it was recently observed that HSV-1 infection is able to promote the degradation of IFI16 in BRCA1-expressing (184B5) but not BRCA1-deficient (HCC1937) mammary epithelial cells (44). BRCA1 is best characterized as a tumor suppressor and is mutated or dysfunctional in a variety of tumor-derived cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…From these observations, we asked the question, "What is the potential role of IFI16 in the life cycle of KSHV that establishes latent infection during de novo infection and maintains its latent infection in the B-lymphoma cells of PEL?" We previously observed that IFI16 is associated with chromatinized latent KSHV and EBV genomes (31,34). However, latent gene expression continues in the presence of IFI16, and viral latency is successfully maintained.…”
mentioning
confidence: 98%
“…IFI16 is a multifunctional DNA binding protein and has been implicated in various cellular functions such as transcriptional regulation, apoptosis, autoimmunity, and cell cycle regulation (25)(26)(27). Studies by us and others have reported the role of IFI16 as a DNA sensor that detects nuclear replicating herpesviral genomes such as KSHV, herpes simplex virus 1 (HSV-1), EpsteinBarr virus (EBV), and bovine herpesvirus 1 (BoHV-1), leading to IFI16 -apoptosis-associated speck-like protein containing a CARD (ASC)-procaspase-1 inflammasome formation that results in the production of the inflammatory cytokine interleukin 1␤ (IL-1␤) (28)(29)(30)(31)(32)(33). We have also shown that IFI16-mediated inflammasomes are activated during prolonged KSHV latency in endothelial and B cells, leading to a constitutive state of IL-1␤ activation (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sensing and binding foreign DNA (15)(16)(17), IFI16 displays multifaceted activity due to its ability to bind to various target proteins (including transcription factors, signaling proteins, and tumor suppressor proteins) and to modulate a multitude of various cell and viral functions (12,13,(18)(19)(20)(21)(22)(23). IFI16 has been shown to interact with the tegument protein pp65 of HCMV at the major immediate-early promoter/enhancer (MIEP) early during infection, resulting in the upregulation of IE protein expression (20).…”
mentioning
confidence: 99%